Taguchi design optimization of curcumin loading in mesoporous silica nanoparticles with variable particle and pore sizes - Mina Shafiee; Samira Sadat Abolmaali; Mozhgan Abedanzadeh; Alimohammad Tammadon (Shiraz University of Medical Sciences, 2022)
Mesoporous silica nanoparticles (MSNs) have received a lot of attention due to their wide range of applications in the delivery of poorly soluble phytochemicals like curcumin (CUR). Given that pore diameter and particle size determine the specific surface area, as well as drug loading in mesoporous nanoparticles, in the present study, we developed MSNs with varying pore sizes to investigate their effects on CUR loading. Dynamic light scattering (DLS), field-emission- scanning electron microscopy (FE-SEM), and Brunauer-Emmett-Teller (BET) analyses were used to characterize the MSNs. CUR was loaded into MSNs using solvent evaporation method, and the drug loading was determined using UV spectroscopy. Results revealed that the MSN synthesis condition had a significant effect on pore size and particle diameter. According to FE-SEM micrographs, MSNs had a nearly spherical shape. DLS results indicated particle sizes ranging from 25 to 100 nm. According to the BET findings, pore size and specific surface area varied in range of 4 - 8 nm and of 570 - 1180 m2/g, respectively. In addition, CUR loading efficiency and loaded amount were 75% and 33% in optimal conditions, respectively. These findings supported the use of MSNs to load and deliver CUR as a poorly soluble drug in a variety of pathophysiological conditions. Keywords: Mesoporous silica nanoparticles, Pore size, Particle size, Surface area, Drug loading, Curcumin. Please cite this article as: Mina Shafiee, Samira Sadat Abolmaali, Mozhgan Abedanzadeh, Ali Mohammad Tamaddon. Taguchi design optimization of curcumin loading in mesoporous silica nanoparticles with variable particle and pore sizes. Trends in Pharmaceutical Sciences. 2022;8(3):155-164. doi: 10.30476/TIPS.2022.95646.1150